Isolation and identification of a novel phage targeting clinical multidrug-resistant Corynebacterium striatum isolates - Wang, Jiao; Zhang, Meng; Pei, Jiao; Yi, Wei; Fan, Li; Wang, Chunhua; Xiao, Xiao (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Over the past decade, Corynebacterium striatum (C. striatum), an emerging multidrug-resistant (MDR) pathogen, has significantly challenged healthcare settings, especially those involving individuals with weakened immune systems. The rise of these superbugs necessitates innovative solutions. Methods This study aimed to isolate and characterize bacteriophages targeting MDR-C. striatum. Utilizing 54 MDR-C. striatum isolates from a local hospital as target strains, samples were collected from restroom puddles for phage screening. Dot Plaque and Double-layer plate Assays were employed for screening. Results A novel temperate bacteriophage, named CSP1, was identified through a series of procedures, including purification, genome extraction, sequencing, and one-step growth curves. CSP1 possesses a 39,752 base pair circular double-stranded DNA genome with HK97-like structural proteins and potential for site-specific recombination. It represents a new species within the unclassified Caudoviricetes class, as supported by transmission electron microscopy, genomic evolutionary analysis, and collinearity studies. Notably, CSP1 infected and lysed 21 clinical MDR-C. striatum isolates, demonstrating a wide host range. The phage remained stable in conditions ranging from -40 to 55°C, pH 4 to 12, and in 0.9% NaCl buffer, showing no cytotoxicity. Discussion The identification of CSP1 as the first phage targeting clinical C. striatum strains opens new possibilities in bacteriophage therapy research, and the development of diagnostic and therapeutic tools against pathogenic bacteria.